George town's heritage battlefront: resolving public space conflicts - Sazali, Muhamad Ferdhaus; Abdul Rahim, Asyirah; Muhamad, Zikri (2024)
The UNESCO World Heritage Site in Malaysia is situated in George Town, Penang. The enclosed area of this protected site has a wide range of historical treasures that act as a deterrence against unauthorized modifications. Traders participate in regular activity within defined settings. Meanwhile, the peripatetic sellers transition from one area to another. However, it is crucial to recognize the existence of vendors and hawkers who participate in illegal activities and use public spaces for their business ventures. The study area has identified a prominent element that contributes to conflicts in public places, namely the substantial demand for street food outlets. The precise geographical coordinates of the combat area have been properly recognized and recorded to facilitate a thorough analysis. The objective of this research is to determine the geographic prevalence and severity of confrontations that occur in public settings. The conservation of the ecosystem is greatly dependent on the accessibility and use of public space.